The efficacy of Aloe vera in the healing process of Pressure Sores: a case study (Research, Society and Development, 2022)
The present study aimed to report the healing process of a LPP treated with Aloe vera-based gel. This is a descriptive case study, with a qualitative approach, developed in a public hospital in the southern region of the state of Tocantins, with a hospitalized patient who presented a stage 4 LPP in the sacral region. Anamnesis, physical exam and monitoring of the lesion's healing process were carried out, using 0.5% Aloe vera gel. The healing process was followed up by means of photographic records on days 0, 30, 75 and 150 of treatment. The results obtained were satisfactory, showing that Aloe vera has great action in the process of repair, healing and tissue hydration. We conclude that the use of Aloe vera, in the treatment of pressure sores, may bring benefits, due to its great healing potential, facilitating the healing and reconstitution of these lesions.